Three-dimensional kinematics and ground reaction forces during the instep and outstep soccer kicks in pubertal players - Katis, A.; Kellis, E. (Journal of Sports Sciences, 2010)
The purpose of the present study was to compare the three-dimensional kinematics of the lower extremities and ground reaction forces between the instep kick and the kick with the outside area of the foot (outstep kick) in pubertal soccer players. Ten pubertal soccer players performed consecutive kicking trials in random order after a two-step angled approach with the instep and the outstep portion of the foot. Three-dimensional data and ground reaction forces were measured during kicking. Paired t-tests indicated significantly higher (P < 0.05) ball speeds and ball/foot speed ratios for the instep kick compared with the outstep kick. Non-significant differences in angular and linear sagittal plane kinematic parameters, temporal characteristics, and ground reaction forces between the instep and outstep soccer kicks were observed (P > 0.05). In contrast, analysis of variance indicated that the outstep kick displayed higher hip internal rotation and abduction, knee internal rotation, and ankle inversion than the instep kick (P < 0.05). Our results suggest that the instep kick is more powerful than the outstep kick and that different types of kick require different types of skill training.